Becoming humanizing educators during inhumane times: Valuing compassion and care above productivity and performance - Grace Inae Blum; Leah Dale (Arizona State University, 2021)
This qualitative inquiry presents a duoethnographic reflection by a pre-service teacher and teacher educator on their individual and collective experiences navigating teaching and learning during the COVID-19 pandemic. Emails of gratitude exchanged between both authors serve as the beginning of their inquiry and analysis. Their narratives reveal the ways in which they experienced humanizing pedagogies, received compassion and care, and engaged in culturally sustaining pedagogies within their teacher preparation program. Implications for reimagining teacher preparation embedded in humanizing pedagogies are explored.